2019
DOI: 10.1111/psyp.13372
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reappraisal during unpleasant picture processing: Subjective self‐report and peripheral physiology

Abstract: Increased attention among the research community in exploring underlying mechanisms of emotion regulation has prompted a growth of experimental works in this field. Empirical studies have mainly focused on self‐reports, brain imaging, and electrophysiological measures, with only a few works exploring peripheral physiology. Additionally, most of such studies have not considered the specific stimuli content, even though prior literature has shown relevant differences in psychophysiological and subjective respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 54 publications
6
22
0
Order By: Relevance
“…These findings support the idea that an intermediate duration (between 6 and 8 s) could prompt relatively stable and significant physiological changes, as has been found with other modalities of affective stimuli. As a consequence, the FMMS excerpts selected in the present study were previously edited by shortening them to 8 s in order to ensure a similar trial duration within the task, being therefore comparable to prior music studies (Gringas et al, 2015;Khalfa et al, 2002), as well as other works using emotional pictures or sounds in diverse paradigms such as passive viewing, aversive conditioning, or cognitive reappraisal tasks (Conzelmann et al, 2015;Fuentes-Sánchez et al, 2019;López et al, 2009). Thus, the first objective was to investigate the correspondence between the subjective ratings obtained in the a priori validation study-with longer and variable excerpts durations (Fuentes-Sánchez et al, 2020)-and those obtained here for the shortened excerpts.…”
Section: Fuentes-sánchez Et Almentioning
confidence: 99%
“…These findings support the idea that an intermediate duration (between 6 and 8 s) could prompt relatively stable and significant physiological changes, as has been found with other modalities of affective stimuli. As a consequence, the FMMS excerpts selected in the present study were previously edited by shortening them to 8 s in order to ensure a similar trial duration within the task, being therefore comparable to prior music studies (Gringas et al, 2015;Khalfa et al, 2002), as well as other works using emotional pictures or sounds in diverse paradigms such as passive viewing, aversive conditioning, or cognitive reappraisal tasks (Conzelmann et al, 2015;Fuentes-Sánchez et al, 2019;López et al, 2009). Thus, the first objective was to investigate the correspondence between the subjective ratings obtained in the a priori validation study-with longer and variable excerpts durations (Fuentes-Sánchez et al, 2020)-and those obtained here for the shortened excerpts.…”
Section: Fuentes-sánchez Et Almentioning
confidence: 99%
“…In laboratory contexts, different affective stimuli, such as pictures (International Affective Picture System [IAPS]; Lang, Bradley, & Cuthbert, 1999), sounds (International Affective Digitized Sounds [IADS]; Bradley & Lang, 2007), words (Affective Norms for English words [ANEW]; Bradley & Lang, 2017), and facial expressions (Ekman & Friesen, 1976) have been used as reliable tools to induce emotions. All of these stimuli are generally part of standardized datasets that provide normative values in different affective dimensions (e.g., hedonic valence and arousal), and have been used in numerous experimental procedures, including passive exposure to affective stimuli (Bradley, Codispoti, Cuthbert, & Lang, 2001; Ciuffini, Stratta, & Marrelli, 2018), emotional anticipation (Sege, Bradley, & Lang, 2014), and emotion regulation (Bernat, Cadwallader, Seo, Vizueta, & Patrick, 2011; Conzelmann, McGregor, & Pauli, 2015; Fuentes-Sánchez, Jaén, Escrig, Lucas, & Pastor, 2019). The use of these stimuli has been essential in the study of brain function (Bermpohl et al, 2006; Ozawa, Kanayama, & Hiraki, 2019), peripheral psychophysiological correlates (Gomez, von Gunten, & Danuser, 2016), as well as subjective evaluations (Bradley, Codispoti, Cuthbert, & Lang, 2001) that are part of emotional reactions.…”
mentioning
confidence: 99%
“…In this regard, both reappraisal and acceptance have been shown to be effective in decreasing electrodermal activity and heart rate responses [27,32,33]. Likewise, reappraisal has also been associated with diminished defensive responses such as the startle reflex [32,34], although the literature shows a lack of agreement in the results [35][36][37][38][39]. Regarding behavioral responses, studies have reported that corrugator activity decreases when participants use reappraisal or acceptance strategies [28].…”
Section: Introductionmentioning
confidence: 99%